Identifikasi Jenis Jamur Basidiomycetes di Kecamatan Patumbak, Binjai Barat, Medan Marelan - Aulia, Ayu Riski; Ulfa, Syarifah Widya; Afrianti, Billah; Sayhafitri, Dini Indah; Khairuddin, Faritz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is an identification study of basidiomycetes mushrooms in Patumbak sub-district, West Binjai and Medan Marelan. This research was carried out for 2 weeks, in May 2023. This research was carried out in the Districts of Patumbak, West Binjai and Medan Marelan. The purpose of this research is as information for the people in the area as information and as education. That in Patumbak District, West Binjai District, Medan Marelan District, there are various types of mushrooms of the basidiomycetes class, some of which can be consumed, can be used as medicine, and some cannot be consumed because they contain poison. The types of Basidiomycetes mushrooms found in the Districts of Patumbak, West Binjai and Medan Marelan are very diverse. The results of this study were the types of fungi found, namely Trametes, Pleurotus, Lactarius, Ganoderma, Fomitopsis, Phaeolus, Cronartium. This is influenced by environmental factors such as temperature, humidity and soil pH. The development and growth of fungi is strongly influenced by environmental factors, including humidity, temperature, soil pH and light intensity. Keywords: Identification, Fungi, Basidiomycetes